2020
DOI: 10.1186/s12889-020-09933-6
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological situation of leprosy in a province in China: a long time to diagnosis and a high rate of deformity

Abstract: Background This epidemiological study aimed to analyse both the distribution and characteristics of leprosy in an endemic province in Northwest China. Methods The medical records of leprosy patients in the province of Shaanxi, China, from 1998 to 2018 were collected from the Chinese Leprosy Management Information System (LEPMIS). Epidemiological variables were analysed in this study. Results A total of 477 new cases were diagnosed between 1998 and 2018 in this region. The average annual detection rate was 0.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…The NCDR of leprosy declined to 0.25 cases per 100,000 population in 2020 from 0.62 cases per 100,000 population in 2011. This downward trend was consistent with the results of studies in other provinces and cities [ 31 ] and the whole country [ 10 ]. This implies that the prevalence of leprosy in Yunnan has been controlled and remains at a low epidemic level.…”
Section: Discussionsupporting
confidence: 92%
“…The NCDR of leprosy declined to 0.25 cases per 100,000 population in 2020 from 0.62 cases per 100,000 population in 2011. This downward trend was consistent with the results of studies in other provinces and cities [ 31 ] and the whole country [ 10 ]. This implies that the prevalence of leprosy in Yunnan has been controlled and remains at a low epidemic level.…”
Section: Discussionsupporting
confidence: 92%
“…New pediatric leprosy cases were more common in males, with a male to female ratio of 1.71:1. Similar results were discovered in a previous study in some provinces, such as Shaanxi in China [ 27 ]. The sex ratio results were also consistent with the findings in other countries or areas [ 15 ].…”
Section: Discussionsupporting
confidence: 91%
“…The experienced long path to diagnosis coincided with worldwide studies on diagnostic delay [ 3 , 5 , 26 ]; Hansen`s disease is often found after many years and therefore with already existing disabilities [ 3 , 27 , 28 ]. In a quantitative study from north-eastern Colombia, the mean delay in diagnosis has been reported to be 33.5 months [ 5 ].…”
Section: Discussionmentioning
confidence: 99%